Effects of Fallow Replacement Crops on Wheat and Grain Sorghum Yields - J. Holman; A. Obour; T. Roberts; S. Maxwell (Kansas Agricultural Experiment Station Research Reports, 2018)
Interest in replacing fallow with a cash crop or cover crop has necessitated research on soil, water, and wheat yields following a shortened fallow period. Fallow stores moisture, which helps stabilize crop yields and reduces the risk of crop failure; however, only 25 to 30% of the precipitation received during the fallow period of a no-till wheat-fallow rotation is stored. The remaining 75 to 70% of precipitation is lost, primarily due to evaporation. Moisture storage in fallow is more efficient earlier in the fallow period, when the soil is dry, and during the winter months when the evaporation rate is lower. It may be possible to increase cropping intensity without reducing winter wheat yield. This study evaluated replacing part of the fallow period with a cover, annual forage, or short-season grain crop. Plant available water at wheat and grain sorghum planting and winter wheat and grain sorghum yields were measured.
Keywords: cover crops; fallow; soil water; crop yield; and flex-fallow